TINJAUAN KRITIS TERHADAP KONSEP AL-ASHIL DAN AL-DAKHIL - Razi, Fahrur (STAI Asy-Syukriyyah, 2024)
This study reviews the concept of al-dakhil wa al-ashil in Qur'anic interpretation, focusing on Shia infiltration. The literature study method is used to explore the concept. The results show that the concept of al-dakhil is an effort to deal with unauthorized interpretation of the Qur'an, especially regarding the influence of external sources. However, the concept is also prone to ideological claims and repetition without innovation. Some passages are even considered as repetition of previous studies without new ideas. Critics of the concept highlight its inability to accommodate diversity. Nonetheless, the concept is important in understanding the history and challenges in Qur'anic interpretation. Further studies are needed to comprehensively understand this concept.